Negative has the little dash in front of it
Thank you hope this helps
Answer:
![20x^{4}-39x^{3} +26x^{2}-6x\\](https://tex.z-dn.net/?f=20x%5E%7B4%7D-39x%5E%7B3%7D%20%2B26x%5E%7B2%7D-6x%5C%5C)
Step-by-step explanation:
Multiply the two polynomials by multiplying each term
![(5x^{2} -6x+2)(4x^{2} -3x)\\5x^2*4x^2+5x^2(-3x)+(-6)*4x^2+(-6x)(-3x)+2*4x^2+2(-3x)\\20x^{4}-39x^{3} +26x^{2} -6x\\](https://tex.z-dn.net/?f=%285x%5E%7B2%7D%20-6x%2B2%29%284x%5E%7B2%7D%20-3x%29%5C%5C5x%5E2%2A4x%5E2%2B5x%5E2%28-3x%29%2B%28-6%29%2A4x%5E2%2B%28-6x%29%28-3x%29%2B2%2A4x%5E2%2B2%28-3x%29%5C%5C20x%5E%7B4%7D-39x%5E%7B3%7D%20%20%2B26x%5E%7B2%7D%20-6x%5C%5C)
f(h(x))= 2x -21
Step-by-step explanation:
f(x)= x^3 - 6
h(x)=\sqrt[3]{2x-15}
WE need to find f(h(x)), use composition of functions
Plug in h(x)
f(h(x))=f(\sqrt[3]{2x-15})
Now we plug in f(x) in f(x)
f(h(x))=f(\sqrt[3]{2x-15})=(\sqrt[3]{2x-15})^3 - 6
cube and cube root will get cancelled
f(h(x))= 2x-15 -6= 2 x-21
Answer:
im confused as you are
Step-by-step explanation:
look so what it is saying its that theres 22 in total. 14 already have a sibling and 18 have a pet. 22-14 is 8 and 22-18 is 4. how are you supposed to find the rest of them who have both?